PERKEMBANGAN SISTEM HUKUM KEPOLISIAN DI INDONESIA DALAM PERSPEKTIF SISTEM PERADILAN PIDANA ANAK - Prasetyo, Wiyono Eko (Sekolah Tinggi Ilmu Kepolisian, 2023)
Basically, the enactment of Law No. 11/ 2012 on the system of Juvenile Justice at providing protection to children who are involved in the mechanism of the system of Juvenile Justice, particularly in the processes of investigation conducted by the police.In the context of law enforcement, the Indonesian National Police must be able to provide proportionally and profesionally to the children who are involved in or suspects of criminal offences. Nevertheless, there are still many irregularities done Polri personnel in general and investigators in-charged with juvenile justice in particular. They treat the children who are involved in or suspects of criminal offences like adults who commits criminal offences.In order to analyze and get the answers for the research problems, the authors employs the Qualitative Research Method, where the legal materials and information are obtained through the documentation study, and interviews with relevant parties.The results of the research conclude that the development System of Police Law in Indonesian (the three sub-systems in the System of Police Law) are closely interrelated with the development System of Juvenile Justice. It has improved the professionalism of Polri’s investigators and to assist Polri in developing the substance of Police Law, Polri’s organizational structure, and change the culture of Polri’s investigators in handling or investigating children who are involved in or suspects of criminal offences.